Description of Sangeeta sinuomacula sp. nov. (Hemiptera: Cicadellidae: Megophthalminae: Agalliini) from Yunnan Province of Southwest China - Li, Hu; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2015)
A new species, Sangeeta sinuomacula Li, Dai & Li sp. nov., of tribe Agalliini of subfamily Megophthalminae (Hemiptera: Cicadellidae) is described and illustrated from Yunnnan Province of Southwest China. The new species is easily distinguished from other Sangeeta species by the aedeagal shaft with a pair of slender processes instead of lamelliform lateral expansions. A key to Sangeeta species and updated checklist with distribution are provided.